Kalium sebagai salah satu keunggulan tempe kedelai lokal Indonesia (varietas Grobogan) dibandingkan tempe kedelai impor - Widiany, Fery Lusviana; Metty, Metty; Widaryanti, Rahayu; Azizah, Shafira Nur (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Potassium is one of the advantages of local Indonesian soybean tempeh (Grobogan variety) compared to imported soybean tempehBackground: Fulfilling high potassium needs can be done by replacing portions of food that have a low potassium content with foods that have a high potassium content, one of which is from legume products or processed products such as tempeh. Indonesian people are considered to prefer imported soybean tempeh products compared to local soybean tempeh, even though local soybean tempeh is thought to have better nutritional content than imported soybean tempeh. Objective: This research was conducted to analyze the potential advantage of local soybean tempeh compared to imported soybean tempeh based on potassium content. Method: This experimental research was carried out in Yogyakarta from June–December 2022. The objects of this research included local soybean tempeh and imported soybean tempeh. The independent variable of this research was the variation between local soybean tempeh and imported soybean tempeh, while the dependent variable was potassium content. Data were analyzed univariately and bivariately using the Independent T-test.Results: The Independent T-Test to analyze the difference in potassium content of local soybean tempeh flour and imported soybean tempeh flour showed a p-value=0.000 (p<0.05), the mean difference between the two groups showed a result of 106.45.Conclusion: The potassium content in local soybean tempeh flour is 106.45 mg/100 g significantly higher than the potassium content in imported soybean tempeh flour.